Simultaneous causality in international trade - Enzo Weber (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
This paper proposes estimating causalities in bilateral international trade in simultaneous systems, including domestic and foreign GDP as well as mutual trade flows. Conventional macroeconomic theory mainly follows partial approaches like import functions or exportled growth. Focusing on the US relations with Euroland and Canada, cointegration analyses however reveal,that the system dynamics, and so both im- and exports, are simply governed by US GDP shocks. In conclusion, exploring sources and effects of international trade should be seen as an inherently empirical task.
Keywords: F10; C32; 330; Import; Export; Causality; Cointegration; Importnachfrage; Exportinduziertes Wachstum; Außenwirtschaft; Kausalanalyse; Konjunktur; Schock; Internationale Wirtschaftsbeziehungen; USA; Kanada; EU-Staaten